PERANAN KEPUASAN KARYAWAN DALAM MEMEDIASI BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN (Studi Kasus Pada PT JasaRaharja (Persero) Cabang Bali) - Mira Hayuningtyas (Jurnal Ekonomi dan Bisnis Jagaditha, 2016)
PT Jasa Raharja (Persero) is one of government company in the field social insurance and compulsory insurance which has the main task of collecting funds from the public through iuran wajib (IW) and sumbangan wajib dana kecelakaan lalu lintas jalan (SWDKLLJ), than distribute funds for the victims of traffict accidents either on land, sea, or the air. Jasa Raharja always trying to improve performance in the field through increased absorption accident compensation payments and an increase in the speed of payment of compensation to the community, and to improve administrative performance through the application of standards of good corporate gocernonce (GCG) in various administrative procedures of the company. The Company expects that employee satisfaction, able to mediate the influence of organizational culture on employee performance.This study aims to examine the mediating role of employee satisfaction in the organizational culture on employee performance. Respondents in this study are all employees of PT Jasa Raharja (Persero) Branch of Bali some 52 peoples. This study is a census research because it uses the entire population be a respondents and then it will be processed using the Partial Least Square (PLS). Based on the analysis results indicate that organizational culture has a significant positive effect on employee satisfaction and performance, and employee satisfaction has a significant positive effect on employee performance. The study also found that employee satisfaction is disable to mediate organizational culture on employee performance. Managerial implications that can be applied on PT Jasa Raharja (Persero) Branch of Bali is to improve the promotion of policies to be more open, honest, and based on factual job performance, while for the supervisor are expected to be able to more understand for all of the job, and able to understand and listen to subordinates so that the employee satisfaction of non-material terms are achieved.